PENERAPAN METODE ACTIVE KNOWLEDGE SHARING PADA PEMBELAJARAN QUR’AN-HADITS UNTUK MENINGKATKAN MINAT BELAJAR SISWA KELAS VII SMP NURUL HADINA KECAMATAN PATUMBAK KABUPATEN DELI SERDANG - Jamaluddin, Trie Ikhsana Maulidya Ginting, Muhammad Firman Maulana (Fakultas Agama Islam, 2022)
The purpose of this study was to find out how the application of the Active Knowledge Sharing method in learning the Qur'an-Hadith, student responses to the application of the Active Knowledge Sharing method in learning the Qur'an-Hadith, and student interest in learning the Qur'an-Hadith by applying the method. Active Knowledge Sharing in class VII SMP Nurul Hadina Patumbak District. This research is a type of descriptive qualitative research which consists of the stages of collecting data, analyzing, and interpreting it objectively, factually, accurately and systematically in explaining, describing and writing as well as reporting the state of the object or data that has been obtained in the form of written and spoken words from people. - people and observable behavior. The research subjects were the Principal, Homeroom Teacher, Qur'an-Hadith Teacher, and Students of SMP Nurul Hadina, Patumbak District, Deli Serdang Regency. The results showed that: 1) The application of the Active Knowledge Sharing method in Qur'an-Hadith learning was carried out with several activities, namely preliminary, core and closing activities in accordance with the planned RPP, for evaluation carried out in the form of active knowledge sharing learning, namely in learning emphasizes the activity of sharing information with fellow students while the teacher only acts as a facilitator and guide. Teachers also apply direct learning strategies with the lecture method; 2) Students' responses to the application of the Active Knowledge Sharing method in learning the Qur'an-Hadith show the enthusiastic attitude of students which is marked by following the Qur'an-Hadith learning process very well. Therefore, students are very interested in participating in this learning at the next meeting, this can be seen in student responses that in general students express interest in participating in this learning at the next meeting; and 2) The students' interest in learning the Qur'an-Hadith is significantly increased which can be indicated by the enthusiasm of students, enthusiasm of students, the sense of pleasure and interest of students in the process of learning the Qur'an-Hadith, this of course cannot be separated from the ways of teaching the teacher. Qur'an-Hadith that facilitates student learning well, comfortable and fun, so that students' interest in learning Qur'an-Hadith can increase very well.